Design and experiment of the comb-brush harvesting machine with variable spacing for oil-tea camellia fruit - Du, Xiaoqiang; Shen, Tengfei; Zhao, Lijun; Zhang, Guofeng; Hu, Anguo; Fang, Shenggao; Cao, Yongqing; Yao, Xiaohua (International Journal of Agricultural and Biological Engineering, 2021)
Oil-tea camellia tree is an important oil plant in China that has long flexible branches. The most challenging feature for the mechanized harvest of oil-tea fruits is that its flower and fruit grow synchronously. In order to improve the harvesting efficiency and avoid damaging the flower bud, a hand-held fruit harvesting machine with a variable spacing comb brush was proposed. The harvesting machine can generate three kinds of actuation to detach fruit when it runs. The main actuation results from the brushing of multiple comb fingers. The other two kinds of actuation result from the beating of comb fingers on the fruits and the branches. The finger spacing of the comb brush can be adjusted consequently through moving the spacing adjusting crossbar. Hence, when the finger spacing is smaller than the diameter of the oil-tea fruit, the fruit is brushed off, but the flower bud and leaf pass through the finger gap. When the finger spacing is bigger than the fruit diameter, the fruit stuck between the fingers is loosened to ensure the continuous operation of the machine. Nylon was used as the material of the brush finger to avoid damage, which can also reduce the overall weight. The dynamic simulation of the harvesting machine was carried out with ADAMS, and the acceleration of the front end of the comb finger and the variation of the finger spacing were analyzed. The prototype of the harvesting machine was built and tested in the field. Field experiment results showed that when the speed of the comb finger drive shaft was 480 r/min, the average harvesting percentage of oil-tea fruit was 80%, and the flower bud was seldom detached, which met the working requirements of oil-tea fruit harvesting. Keywords: oil-tea camellia fruit, harvesting machine, variable spacing, comb brush, simulation analysis DOI: 10.25165/j.ijabe.20211401.5703 Citation: Du X Q, Shen T F, Zhao L J, Zhang G F, Hu A G, Fang S G, et al. Design and experiment of the comb-brush harvesting machine with variable spacing for oil-tea camellia fruit. Int J Agric & Biol Eng, 2021; 14(1): 172–177.